Byzantinische Zeitschrift (De Gruyter, 1892)
The Byzantinische Zeitschrift is the leading journal in the field of Byzantine Studies. It publishes articles and reviews on all aspects of Byzantine literature, history, society, and culture. Each issue of the journal contains a large bibliographic section. This so-called III. Abteilung serves as the standard bibliography in Byzantine Studies.